2013
DOI: 10.1186/1471-2164-14-480
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin induces different cellular and molecular chemoresistance patterns in colorectal cancer cell lines of identical origins

Abstract: BackgroundCancer cells frequently adopt cellular and molecular alterations and acquire resistance to cytostatic drugs. Chemotherapy with oxaliplatin is among the leading treatments for colorectal cancer with a response rate of 50%, inducing intrastrand cross-links on the DNA. Despite of this drug’s efficiency, resistance develops in nearly all metastatic patients. Chemoresistance being of crucial importance for the drug’s clinical efficiency this study aimed to contribute to the identification and description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…The role of elevated NF-κB activity in the resistance of CRC cells to OXA-induced cell death was previously demonstrated 30 and in agreement with other studies 40 , results presented here indicate that NF-κB is constitutively active in all the CRC cell lines examined; however, we found that those cell lines with acquired resistance to OXA exhibited an increased activation of this pathway as compared to their matched sensitive parental cells, especially the HTOXAR3 resistant model, suggesting a role for NF-κB and its downstream targets in the development of the drug-resistant phenotype. This fact was reported to be associated with the acquisition of a mesenchymal phenotype along the OXA-resistance acquisition process 41 42 and according to this, our exploratory functional enrichment analysis revealed EMT as one of the top hallmarks in the list of genes that were up-regulated in HTOXAR3 cell line in comparison with HT29 cells ( Supplementary Table S3 ). Therefore our results could be explained in part by an EMT process in OXA resistant cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The role of elevated NF-κB activity in the resistance of CRC cells to OXA-induced cell death was previously demonstrated 30 and in agreement with other studies 40 , results presented here indicate that NF-κB is constitutively active in all the CRC cell lines examined; however, we found that those cell lines with acquired resistance to OXA exhibited an increased activation of this pathway as compared to their matched sensitive parental cells, especially the HTOXAR3 resistant model, suggesting a role for NF-κB and its downstream targets in the development of the drug-resistant phenotype. This fact was reported to be associated with the acquisition of a mesenchymal phenotype along the OXA-resistance acquisition process 41 42 and according to this, our exploratory functional enrichment analysis revealed EMT as one of the top hallmarks in the list of genes that were up-regulated in HTOXAR3 cell line in comparison with HT29 cells ( Supplementary Table S3 ). Therefore our results could be explained in part by an EMT process in OXA resistant cells.…”
Section: Discussionsupporting
confidence: 63%
“…Three NF-κB-transcriptionally regulated CXC-chemokines, CXCL8 , CXCL1 and CXCL2 , were highly overexpressed as a result of OXA-resistance acquisition in the HTOXAR3 cell line and at the same time were specifically down-regulated after treatment with OXA plus Curcumin in these cells. These pro-inflammatory chemokines play an important role in regulating CRC progression, angiogenesis and metastasis 51 , processes that have been associated with OXA resistance 42 . The effect of chemotherapy on CXCL8 52 53 , CXCL1 and CXCL2 54 gene transcription has been described elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…EMT has been associated with chemoresistance to several chemotherapeutic agents including paclitaxel [ 36 ], oxaliplatin [ 37 ], gemcitabine [ 38 ], 5-fluororacil [ 39 ] as well as targeted therapies such as tamoxifen [ 40 ], erlotinib and PI3K/Akt inhibitors [ 21 ]. RNA-based multiplex predictors such as Oncotype Dx Recurrence Score and MammaPrint have been effectively transitioned to clinical use; thus, it would be important to determine whether a RNA- or protein-based predictor can indeed have predictive utility.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity evaluations were done with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test (Sigma-Aldrich) for HT-29, DLD-1, CSC and LIV cells. The 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2 H -tetrazolium/phenazine methosulfate (MTS/PMS) (Promega Corporation, Madison, WI, USA) colorimetric cell proliferation assay was done on normal human lymphocytes, following a protocol established previously [ 49 ]. Briefly, cells were seeded in triplicate in 96-well flat-bottom plates, at a cell population density of 2 × 10 4 and 15 × 10 3 for MTT and MTS/PMS assays, respectively.…”
Section: Methodsmentioning
confidence: 99%